Happy place [large type] - Henry, Emily (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"Harriet and Wyn have been the perfect couple since they met in college. Except they broke up five months ago and still haven't told their best friends. Which is how they find themselves sharing a bedroom at the Maine cottage that has been their friend group's yearly getaway for the last decade. Their annual respite from the world, where for one vibrant, blissful week they leave behind their daily lives. Only this year, the cottage is for sale and this is the last week they'll all have together in this place. They can't stand to break their friends' hearts, and so they'll play their parts. After years of being in love, how hard can it be to fake it for one week?"--